PENGUATAN KINERJA PEGAWAI DITINJAU DARI ASPEK DUKUNGAN KEPEMIMPINAN, CAPACITY BUILDING DAN GOOD GOVERNANCE (Studi Kasus pada Sekretariat DPR Kabupaten Pidie Jaya) - Nasruddin, Nasruddin; Iba, Zainuddin; Musrizal, Musrizal (Ekonomika Journal, 2025)
This study aims to examine the background of leadership, capacity development, and good governance in strengthening employee performance. The study was conducted at the DPR secretariat of Pidie Jaya Regency. This type of research is quantitative and uses a causality analysis method. The data analysis technique used is path analysis using SMART-PLS. The results of the analysis show (1) aspects of leadership, capacity development and good governance provide positive support for strengthening employee performance by 23.9%, 19.6% and 31.2% respectively. (2) The leadership factor through good governance contributes to improving performance by 10.8% while through capacity development it has a positive effect on strengthening performance by 14.1%. (3) aspects of capacity development through good governance have a positive impact on strengthening employee performance by 13.2% and (4) simultaneously policies, capacity development and good governance contribute to strengthening employee performance by 28%.